ИНФОРМАЦИЯ ҚӘЎИПСИЗЛИГИ ПӘНИН АРАЛЫҚТАН ОҚЫТЫЎ УШЫН ДИДАКТИКАЛЫҚ МАТЕРИАЛЛАР ЖАРАТЫЎ МӘСЕЛЕЛЕРИ - Турениязова, А.И.; Каналиева, Н.Н. (SCIENCE and SOCIETY, 2017)
In the article the author considers the issues of distance learning as a form of organization of self-study, independent work of students and didactical requirements to the electronic educational resources in the subject “Information security”.
Keywords: distance learning; didactical requirements; electronic educational resources; hypertext; information security